A shear flow instability in plasma sheet region - Kakad, Amar; Lakhina, G. S.; Singh, S. V. (My University, 2003)
A shear flow instability is studied in the plasma sheet region in three component cold plasma consisting of electrons, protons and oxygen ions. The linear dispersion relation is derived with velocity shear in each component, i.e. electrons, protons and oxygen ions. The dispersion relation is solved for the case of O+ ion beam with shear flow passing through stationary electron–ion plasma. It is found that low-frequency waves could become unstable due to the velocity shear of the O+ ion beam in the near earth plasma sheet region. The typical growth rate of the instability is found to be Full-size image (<1 K) with parallel and perpendicular wavelengths ranging from (11–200)RE and Full-size image (<1 K), respectively.
Keywords: Shear flow instability; Magnetic storms; Low frequency waves; Plasma sheet; Magnetic substorms